2006
DOI: 10.1080/15022250600866282
|View full text |Cite
|
Sign up to set email alerts
|

Mobility, Migration and Seasonal Tourism Employment: Evidence from Swedish Mountain Municipalities

Abstract: In recent research it has been shown that a large share of the tourism work force in the Swedish mountain municipalities have their permanent place of residence outside of daily commuting distance from the municipality where they work. In this study, tourism labour mobility and migration to two Swedish mountain municipalities, Åre and Malung, is examined. The principal question addressed is whether temporal tourism labour migration leads to permanent migration of tourism workers or not. The research is based o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(49 citation statements)
references
References 38 publications
1
48
0
Order By: Relevance
“…In addition, although the permanent population of the Swedish mountain region is decreasing, tourism development has led to increased seasonal labour migration. The relationship between seasonal tourism employment and permanent migration was a~dressed by Lundmark (2006) in a more recent study of the Are and Malung munidpalities. 26 Results indicated that relatively few people were involved in temporary labour migration because of tourism employment in the munidpalities permanently migrate to the mountain municipalities, but that tourism sector employment is important for the in-migration of longdistance commuters to the case munidpalities.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…In addition, although the permanent population of the Swedish mountain region is decreasing, tourism development has led to increased seasonal labour migration. The relationship between seasonal tourism employment and permanent migration was a~dressed by Lundmark (2006) in a more recent study of the Are and Malung munidpalities. 26 Results indicated that relatively few people were involved in temporary labour migration because of tourism employment in the munidpalities permanently migrate to the mountain municipalities, but that tourism sector employment is important for the in-migration of longdistance commuters to the case munidpalities.…”
Section: Introductionmentioning
confidence: 98%
“…The reasons for this lie in a variation of the distance decay effect by which the majority ofleisure tourists undertake travel in the urban hinterland on a day-tour basis, with the number of overnight stays and travel declining as a function of distance in relation to the source region (Hall 2006). The notable exception to such a situation is the existence of spedfic purpose resorts (e.g., ski resorts) or desirable amenity locations such as coastal or mountain area, which provide a focal point for tourism-related mobility in non-urban areas (Mtiller 2006a;Lundmark 2006). Pearce (1998: 166) gives several examples of the presence of the 'funnelling effect' whereby tourist visits remain concentrated either along the seafront or clustered together in the central dty area.…”
Section: Introductionmentioning
confidence: 99%
“…However, from the perspective of migrant workers, seasonality may be an attractive feature of the industry. Empirical studies suggest that seasonality may not be considered problematic by some businesses (Duvall, 2004) or employees who accept working just a part of the year (Lundtrop et al, 1999;Andriotis & Vaughan, 2004;Lee-Ross, 1999;Lundmark, 2006). Certainly it does create notions of temporariness which in turn has an impact on the migrant experience.…”
Section: Inmentioning
confidence: 99%
“…International lifestyle migration to such northern locations, and in particular the role of winter in migration and business decisions, is still a very under-researched topic, with most studies focusing on tourism-related international migration from northern countries to southern, warm-weather destinations (Buller & Hoggart, 1994;Casado-Díaz, 2006;Lardiés, 1999;Madden, 1999;Stone & Stubbs, 2007). While some studies have identified winter sports activities, such as alpine skiing, as important drivers of migration (at least on a seasonal basis), they have predominantly focused on popular winter resorts where tourism is well established and (seasonal) work or business opportunities are plentiful (Lundmark, 2006;Tuulentie & Heimtun, 2014). In contrast, consumptive and productive interests around winter experiences in low-amenity areas will likely centre around different values and activities that are currently not well understood.…”
Section: Conceptual Frameworkmentioning
confidence: 99%